(untitled) (Res Medica, 2014)
• Human Nutrition and Dietetics. Davidson and Passmore. E. & S. Livingstone Ltd., Edinburgh. • Simpson and Syme of Edinburgh. John A. Shepherd. Livingstone. 50s. • Notes for the Guidance of Parents of Diabetic Children. J. W. Farquhar. • Early Difficulties with Young Families. Charlotte Himsworth. H. K. Lewis. 45s. • Modern Trends in Obstetrics. Edited R. J. Kellar. Butterworth. 64s. • British Medical Bulletin. “ Immunization Against • Infectious Diseases”. Volume 25, Number 2, May 1969. £2. • Attachment of the Young. F. V. Smith. Oliver & Boyd. 7s. 6d. • Modern Trends in Gynaecology. Edited R. J. Kellar. Butterworth. 64s. • Primer of Histopathological Technique. Geoffrey G. Brown. Butterworth. 52s.